Generations of freedom : gender, movement, and violence in Natchez, 1779-1865 - Ribianszky, Nik (University of Georgia Press, 2021)
"In Generations of Freedom: Gender, Movement, and Violence in Natchez, 1779-1865, Nik Ribianszky employs the lenses of gender and violence to examine family, community, and the tenacious struggles by which free Blacks claimed and maintained their freedom under shifting international governance, from Spanish colonial rule (1779-1795), through American acquisition (1795) and eventual statehood (established in 1817), and finally to slavery's legal demise in 1865"-- Provided by publisher.
Keywords: Free African Americans -- Mississippi -- Natchez.; African American women -- Violence against -- Mississippi -- Natchez.; African American women -- Abuse of -- Mississippi -- Natchez.; Noirs américains affranchis -- Mississippi -- Natchez.; Noires américaines -- Violence envers -- Mississippi -- Natchez.; African American women -- Violence against; Free African Americans; Mississippi -- Natchez; History.